Relationship between Work-Family Conflict, Job Embeddedness, Workplace Flexibility, and Turnover Intentions - Afsar, Bilal; Rehman, Zia Ur (UI Scholars Hub, 2017)
The present study seeks to propose and test a research model that investigates job embeddedness as a mediator and workplace flexibility as a moderator of the effect of family-work conflict on turnover intentions. This study uses a survey method and a structured questionnaire to collect data from 187 nurses working in various hospitals in Islamabad, Pakistan. The results showed that on-the-job embeddedness partially mediated the effect of work-family conflict on nurses’ turnover intention. Furthermore, workplace flexibility moderated the relationship between work-family conflict and turnover intention. Management of the hospitals should take decisive steps to establish and maintain a supportive and flexible work environment because such an environment would help nurses to balance their work (family) and family (work) roles and lead to increased job embeddedness. Otherwise, it would be very difficult to retain high performing nurses in the workplace. The current study contributes to the existing knowledge base by testing job embeddedness as a mediator and workplace flexibility as a moderator of the impact of work-family conflict on turnover intentions of nurses.